Homocysteine, Carotid Intima Media Thickness and NIHSS Score: Clinical Relevance in Indian Stroke Patientspatients - Vatsal Navin Jain; Priyanka Rana; Kshitij Arun Bhoge; Swati Ghanghurde; Mahesh B Phad; Mohit Vijay Rojekar (Babol University of Medical Sciences, 2024)
Background: Stroke is one of the leading causes of mortality and morbidity worldwide accounting for 85% of global deaths from stroke. This study aimed to evaluate the role of homocysteine (HCY) in modulating various stroke parameters and its with carotid intima-media thickness (IMT). Methods: 78 patients of radiology-confirmed acute ischemic stroke were recruited for this study and National Institutes of Health Stroke Scale (NIHSS) score was evaluated upon admission. Blood samples were tested for serum HCY, fasting blood glucose (FBG) and lipid profile. Ultrasonography of neck ascertained IMT of Common (CCA) and Internal carotid artery (ICA). Results: Average age of male and female subjects was 57.88 ± 13.97 & 59.16 ± 13.62 years respectively. 71.93% of stroke patients were hyperhomocysteinemic (HHcyc) and 24.36% were hyperlipidemic. Patients with NIHSS ≥ 5 had higher low-density lipoprotein cholesterol (LDLC) than those with NIHSS < 5. HCY cutoff of ≥ 15 μmol/L had 91.7% sensitivity & 66.7% specificity for predicting. HHcyc state was associated with increased ICA IMT. HHcyc state was best predicted by ICA IMT with which it is positively correlated (P-Value = 0.012). Conclusion: HHcyc state holds a good predictive value for severity of stroke. We also came to a conclusion that ICA IMT measurement may also reduce the need for a homocysteine test as it predicts higher HCY levels; this will reduce the burden on resources. We suggest that evaluating HCY and ICA IMT should be made part of the standard protocol for management of stroke.